Parental involvement in school activities and student reading achievement - theoretical perspectives and PIRLS 2011 findings - Klemenčič, Eva (Šolsko polje, 2014)
Enhancing parental involvement is a major concern for policymakers in education in many countries. Literature review has exposed strong connections between parental involvements in school activities and student outcomes (also achievements). For exploring the association between parental involvement in school activities and student reading achievement, we used data from the latest cycle of the Progress in International Reading Literacy Study (PIRLS 2011) conducted by the International Association for the Evaluation of Educational Achievement (IEA). The study assesses reading literacy at Grade 4 using representative samples of students in the participating education systems. PIRLS also collects extensive, internationally comparable informationon the background characteristics of the students, their parents, teachers and the schools where they study. We conducted the analyses utilizing information on parental involvement in school activities (as reported by school principals), parental level of education (as reported by parents), and student reading achieve ment (PIRLS achievement scores). We used data from 54 of 56 education systems that included all relevant data needed for the analyses. Regarding that, this paper seeks to answer two questions. First, is there a relationship between parental involvement in school activities and student reading achievement in the education systems participating in PIRLS 2011? Given that both parental involvement and student achievement are often influenced by the family socio-economic context, the second question is whether parental involvement is associated with the level of parental education within each of the analysed education systems? This paper presents evidence demonstrating that within most of the 54 education systems we analysed, parental involvement in school activities is positively associated with student performance in PIRLS 2011. That is to say, students enrolled in schools with higher parental involvement tend to have higher reading achievement. It also shows that the level of parental involvement in school is positively associated with the level of parental education. Thus, parents with lower education levels are likely to participate less in school and vice versa. The conclusions suggest that the promotion of parental involvement may be an effective strategy for increasing reading achievement, and policies in this direction are particularly relevant for schools with students whose parents have lower levels of education.
Keywords: PIRLS; mednarodne raziskave; branje; bralna pismenost; starši; preverjanje znanja; učenci; osnovne šole